2023
DOI: 10.1126/scitranslmed.adg7020
|View full text |Cite
|
Sign up to set email alerts
|

Intervertebral disc human nucleus pulposus cells associated with back pain trigger neurite outgrowth in vitro and pain behaviors in rats

Wensen Jiang,
Juliane D. Glaeser,
Giselle Kaneda
et al.

Abstract: Low back pain (LBP) is often associated with the degeneration of human intervertebral discs (IVDs). However, the pain-inducing mechanism in degenerating discs remains to be elucidated. Here, we identified a subtype of locally residing human nucleus pulposus cells (NPCs), generated by certain conditions in degenerating discs, that was associated with the onset of discogenic back pain. Single-cell transcriptomic analysis of human tissues showed a strong correlation between a specific cell subtype and the pain co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…Moreover, further distinctions between the types of NPCs and their differentiation pathways have been found to be linked to certain pathologies and symptoms [ 87 , 88 , 89 ]. For example, Jiang et al [ 90 ] identified a specific MMP3+, SLC7A2+, and TM4SF1+ NPC clusters associated with symptomatic low back pain. In contrast, Han et al [ 91 ] revealed up to seven diverse NPC populations.…”
Section: Cellular Composition Of Notochord To Npmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, further distinctions between the types of NPCs and their differentiation pathways have been found to be linked to certain pathologies and symptoms [ 87 , 88 , 89 ]. For example, Jiang et al [ 90 ] identified a specific MMP3+, SLC7A2+, and TM4SF1+ NPC clusters associated with symptomatic low back pain. In contrast, Han et al [ 91 ] revealed up to seven diverse NPC populations.…”
Section: Cellular Composition Of Notochord To Npmentioning
confidence: 99%
“…This process is further associated with the progression of IDD and low back pain. Notably, there are clear distinctions among the populations identified between different studies [ 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. This warrants further careful investigations and calls for an evidence-based consensus within the spine community, providing a valuable basis for a future review.…”
Section: Cellular Composition Of Notochord To Npmentioning
confidence: 99%
“…Chronic inflammation from IVDD is a strong contributor to progressive degenerative conditions and pain. This is due to the known roles that pro-inflammatory cytokines play in increased matrix catabolism, neurovascular ingrowth into the IVD, and enhanced nociception ( 714 ). Furthermore, infiltration of cytokine-releasing macrophages into the peripheral nervous system and damaged IVD has been observed, suggesting a correlation between immune cell infiltration and discogenic pain ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most common and repeatable method for achieving intervertebral disc (IVD) degeneration is a physical injury of the annulus fibrosis using needle puncture (10,14,15). Scraping or surgical blade incision of the annulus fibrosis, injections of inflammatory mediators, DRG or facet joint compression, or applications of various substances (e.g., nucleus pulposus fragments) into discs have also been used to induce IVD injury and/or related pain symptoms (16)(17)(18)(19)(20)(21)(22)(23)(24). Partial penetration of the annulus fibrosis induces a slower degenerative process (reduced IVD height and slowly increasing degeneration) than a full penetration (rapid nuclear avulsion but no degeneration) (10, 13), with the former more closely reproducing the human condition of progressive pathology (14).…”
Section: Introductionmentioning
confidence: 99%